CTA initiative on West African fish production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
In West Africa there is an urgent need to increase the value of fish products, both to boost consumption and to bring in more cash to communities whose livelihoods depend on fishing. Meetings in Banjul and Freetown initiated by CTA have resulted in...